Comparison of static and dynamic in vitro digestion models to estimate the bioaccessibility of lutein in lutein-rich foods - Lee, Eun Ha; Cha, Kwang Hyun; Trang Thi Vuong; Kim, Sang Min; Pan, Cheol-Ho (KOREAN SOC APPLIED BIOLOGICAL CHEMISTRY, 2018)
This study aimed to determine the bioaccessibility of lutein in lutein-rich food, using static and dynamic models of in vitro gastrointestinal digestion. Here, kale powder (KP) and lutein supplement (LS) were used as representative lutein-rich foods. The bioaccessibility of lutein from KP did not considerably differ between static (59.92%) and dynamic (56.08%) digestion. Bioaccessibility was consistently maintained at the same level during dynamic digestion. The amount of lutein released from the LS during dynamic digestion was five times higher than that released during static digestion (67.88 vs 12.34%). The results showed that (a) bioaccessibility of lutein was affected by various factors such as food source, solid:liquid ratio, and interaction with dietary components, and (b) dynamic digestion should be suitable for evaluating the bioaccessibility of lutein in high-fat foods.
Keywords: COMPUTER-CONTROLLED MODEL; VITAMIN-E; EARLY ATHEROSCLEROSIS; DIETARY CAROTENOIDS; SMALL-INTESTINE; BETA-CAROTENE; CACO-2 CELLS; BIOAVAILABILITY; VALIDATION; VEGETABLES